Dirac cone protected by non-symmorphic symmetry and three-dimensional Dirac line node in ZrSiS - Leslie M. Schoop (Nature Portfolio, 2016)
The family of topological materials has been growing rapidly but most members bare limitations hindering the study of exotic behaviour of topological particles. Here, Schoop et al. report a Fermi surface with a diamond-shaped line of Dirac nodes in ZrSiS, providing a promising candidate for studying two-dimensional Dirac fermions.